Chaihu Longgu Muli Decoction inhibits chronic stress-induced lung cancer epithelial-mesenchymal transition process by suppressing Rap1/ERK signal pathway - Li, Zibo; Huang, Ziyang; Wang, Zhiyi; Guo, Zhenzhen; Wang, Baoying; Li, Yucheng; Xu, Erping (Frontiers in Pharmacology, 2025)
BackgroundChaihu Longgu Muli Decoction (CLM) is a classical herbal formula originally documented in Shang Han Lun. With an 1800-year clinical history, CLM remains widely prescribed for depression (“Yu Zheng” in Traditional Chinese Medicine theory). Emerging evidence suggests that chronic stress-induced depression is closely linked to lung cancer progression and metastasis. However, the therapeutic potential of CLM in this context remains unexplored.MethodsA lung cancer cell xenograft model combined with chronic unpredictable mild stress (CUMS) was used to evaluate the effect of CLM on lung cancer growth. Proteomic analysis was performed to explore the underlying mechanisms by which CLM alleviates CUMS-induced lung cancer progression. Western blot and qPCR were conducted to detect changes in Rap1/ERK-mediated epithelial-mesenchymal transition (EMT) progression. Finally, Rap1 agonists were utilized to determine the therapeutic mechanism of CLM on cortisol or corticosterone (Cort)-induced EMT progression in lung cancer cells and a mouse lung cancer model.ResultsIn our study, CUMS promoted lung cancer xenograft growth, increased the expression of the proliferation marker Ki67, and elevated serum Cort levels. CLM treatment not only alleviated CUMS-induced depression-like behaviors, but also suppressed stress-driven tumor growth. These effects were replicated in a urethane-induced lung cancer model combined with CUMS. Proteomic analysis revealed that CLM’s anti-tumor effects were associated with modulation of the Rap1 pathway. Mechanistically, CUMS downregulated Rap1GAP, activating Rap1 and subsequent ERK1/2 phosphorylation, thereby promoting EMT in lung cancer tissues. CLM effectively reversed these effects by inhibiting Rap1/ERK-mediated EMT. In vitro, CLM suppressed cortisol-induced migration, invasion, and EMT in lung cancer cells, and these effects were attenuated by Rap1 agonists. Furthermore, CLM inhibited Cort-induced EMT and depression-like behaviors in vivo, while Rap1 activation diminished CLM’s efficacy against Cort-driven tumor growth.ConclusionThese findings suggest that Rap1/ERK-mediated EMT is a hallmark of chronic stress-associated lung cancer progression. CLM exerts its therapeutic effects by targeting this pathway, offering a novel strategy to mitigate stress-aggravated oncogenesis.